Evaluation of efficiency of nested multiplex allele‐specific PCR assay for detection of multidrug resistant tuberculosis directly from sputum samples. (1st May 2016) - Mistri, S.K.; Sultana, M.; Kamal, S.M.M.; Alam, M.M.; Irin, F.; Nessa, J.; Ahsan, C.R.; Yasmin, M.
Abstract: For an effective control of tuberculosis, rapid detection of multidrug resistant tuberculosis (MDR‐TB) is necessary. Therefore, we developed a modified nested multiplex allele‐specific polymerase chain reaction (MAS‐PCR) method that enables rapid MDR‐TB detection directly from sputum samples. The efficacy of this method was evaluated using 79 sputum samples collected from suspected tuberculosis patients. The performance of nested MAS‐PCR method was compared with other MDR‐TB detection methods like drug susceptibility testing (DST) and DNA sequencing. As rifampicin (RIF) resistance conforms to MDR‐TB in greater than 90% cases, only the presence of RIF‐associated mutations in rpoB gene was determined by DNA sequencing and nested MAS‐PCR to detect MDR‐TB. The concordance between nested MAS‐PCR and DNA sequencing results was found to be 96·3%. When compared with DST, the sensitivity and specificity of nested MAS‐PCR for RIF‐resistance detection were determined to be 92·9 and 100% respectively. Significance and Impact of the Study: For developing‐ and high‐TB burden countries, molecular‐based tests have been recommended by the World Health Organization for rapid detection of MDR‐TB. The results of this study indicate that, nested MAS‐PCR assay might be a practical and relatively cost effective molecular method for rapid detection of MDR‐TB from suspected sputum samples in developing countries with resource poor settings.